Morphology of Settlement of the Dayak Kenyah Tribe, Budaya Pampang Village, Samarinda City in a Socio-Cultural Context - Nabela, Siela Mara; Titisari, Ema Yunita; Utami, Sri (University of Merdeka Malang, 2023)
The Dayak Kenyah community is a dynamic tribe influenced by its socio-cultural context. Socio-cultural changes will affect the form of settlement. This journal focuses on the influence of the socio-cultural context on the settlement morphology of the Dayak Kenyah tribe in the Budaya Pampang Village to get meaning in forming their settlements. This study uses Levi-Strauss structuralism to see the meaning behind the relationship between the spatial morphology of settlements and socio-culture from data collection results such as physical evidence, interviews, and questionnaires. The results of this study found the meaning of defense, togetherness and kinship, spirituality, harmony with nature, and adaptation in the spatial formation of Dayak Kenyah settlements.